2021
DOI: 10.1093/pm/pnab005
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Cognitive Performance among People with Chronic Use of Opioids for Chronic Non-Cancer Pain

Abstract: Objective Opioids, often prescribed for chronic non-cancer pain, may adversely affect cognition. Research has not been synthesised in recent years, during which time academic interest has increased. This study presents meta-analyses on cognitive performance in people taking opioids for CNCP. Methods We ran systematic literature searches in EMBASE, Medline, and PsycINFO. Eligible studies included people taking opioids for CNCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the other hand, opioid therapy for chronic non-cancer pain does not affect cognitive performance and even improves it in certain domains. Attention and memory deficits are probably more pain-related than opioid use 41 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, opioid therapy for chronic non-cancer pain does not affect cognitive performance and even improves it in certain domains. Attention and memory deficits are probably more pain-related than opioid use 41 .…”
Section: Discussionmentioning
confidence: 99%
“…'Difficulty with mental activities' and 'poor memory' are described by 23% and 17% of the patients of this survey, respectively. The correlation between chronic opioid use and cognition is still inconsistent in the literature despite a large body of research; whereas some reviewers describe minimal or no significant impairment in cognitive functioning (Akhurst et al, 2021;Ersek et al, 2004), others found reduced attention, vigilance, working memory and psychomotor speed (Allegri et al, 2019;Jamison & Edwards, 2013) depending on the characteristics of the opioid (e.g. the chemical structure, formulation, dosing, treatment phase: beginning or steady state, comedication of anti-depressants/anti-epileptic drugs) or the patient (e.g.…”
Section: Discussionmentioning
confidence: 99%